2019
DOI: 10.1055/s-0039-1688555
|View full text |Cite
|
Sign up to set email alerts
|

Is It Better to Routinely Use Tourniquet for Knee Arthroscopic Surgery: A Systematic Review and Meta-analysis

Abstract: The use of tourniquet in knee arthroscopic surgery is a routine technique and provides convenience for the operation. However, the adverse effects caused by tourniquet during the operation are noticed by more and more researchers. The purpose of our study was to perform a systematic review and meta-analysis to assess the effects of tourniquet use in knee arthroscopy. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines, we searched databases like PubMed, Cochrane library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, knee arthroscopy can be performed without a tourniquet or under a tourniquet. 20 The potential advantages and disadvantages of these methods are beyond the scope of our study. In our clinic, we routinely perform knee arthroscopy under a tourniquet.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, knee arthroscopy can be performed without a tourniquet or under a tourniquet. 20 The potential advantages and disadvantages of these methods are beyond the scope of our study. In our clinic, we routinely perform knee arthroscopy under a tourniquet.…”
Section: Discussionmentioning
confidence: 92%
“… 257 A more recent systematic review and meta-analysis suggested that the visualization benefit was more historic and that when directly compared, the use of a no tourniquet for simple knee arthroscopy resulted in decreased post-operative opioid requirement and less post-operative blood loss with no difference in operative time, post-operative pain score between groups, or post-operative functional strength. 258 …”
Section: Recommendations Regarding Arthroscopymentioning
confidence: 99%
“…257 A more recent systematic review and meta-analysis suggested that the visualization benefit was more historic and that when directly compared, the use of a no tourniquet for simple knee arthroscopy resulted in decreased post-operative opioid requirement and less post-operative blood loss with no difference in operative time, post-operative pain score between groups, or post-operative functional strength. 258 Tranexamic acid has been found to reduce post-operative swelling, hemarthrosis incidence, and improve early postoperative function in total joint arthroplasty. 259 As such its use in knee arthroscopy has increased in use as a mechanism to both improve visualization and decrease symptomatic post-operative hemarthrosis.…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…Compared with the study of Schwab et al, patients' HBL after BOWHTO in our study was not only lower than that of TKA patients but also significantly higher than that of UKA. The HBL after BOWHTO is much higher than the dominant blood loss, which is closely related to the surgical method of osteotomy itself; factors such as intraoperative release of soft tissue, unsealed osteotomy sectioning, and routine application of tourniquet are the key factors that cause recessive blood loss [9,18]. In clinical practice, we often find that patients can experience noticeable silt and redness at the distal end of the incision at 3-5 days after surgery that may even be combined with wound oozing, which is often caused by the accumulation of HBL under the skin and is a potential risk of wound infection.…”
Section: Comparison With Other Knee Operationsmentioning
confidence: 99%